Effectiveness of the Selection of Village Devices in Brebes Regency Based on Regulation Number 100 Of 2020 - Diryo Suparto; Akhmad Habibullah (Budapest International Research and Critics University, 2021)
Preparing village apartments with the skills and credibility to achieve these goals makes the Brebes Regency Government prepare special instruments to lift and stop village devices in the Brebes Regency government environment through Brebes Regent Regulation No. 100 of 2020 concerning the Appointment and Dismissal of Village Devices. This study uses qualitative methods with a deprepretental approach to explaining various phenomena when implementing village-level regulations. The location of this study is in the villages of Randusanga Wetan and Randu Sanga Kulon in Brebes Subdistrict, Brebes Regency. One of the mandatory requirements in the code in article 8 of the government must cooperate with third parties, who certainly have the competence to hold the exam in question invited by the law. Unfortunately, it is not clear in detail which third-party entities are in question. The study results showed some obstacles such as the lack of computer facilities in the village and so on.